PEMBERDAYAAN MASYARAKAT SEKOLAH MELALUI SOSIALISASI MANFAAT MENGKONSUMSI BUAH DAN SAYUR DI MADRASAH IBTIDAIYAH SWASTA AL ISTIQAMAH, KUEH LHOKNGA, ACEH BESAR - Farrah Fahdhienie; Tahara Dilla Santi (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2024)
Elementary school children are in a critical period of growth and development. Proper nutritional intake, especially from vegetables and fruit, is very important to support their health, strengthen the immune system, and prevent disease. Increasing knowledge about the benefits of consuming fruit and vegetables needs to be done in order to prevent various diseases related to nutrition and optimize growth and development. The method used was health education for 31 Mis students. This activity begins with distributing pre-test questionnaires, counseling and ends with distributing post-test questionnaires. The results of this activity show that the outreach activities related to the benefits of consuming fruit and vegetables were carried out well and almost 70% experienced an increase in knowledge. In conclusion, there was an increase in knowledge after counseling was carried out through presentations and screening of educational videos.